Talking About Childhood Obesity. (March 2022) - Wagner, Ellen; Jamil, Omar; Hodges, Bethany
While discussing obesity with pediatric patients and their families can be difficult, it is an essential step toward appropriate weight management. There is paucity of data regarding language preferences when discussing obesity in this population. In this pilot qualitative study, we interviewed 8 parents of patients diagnosed with obesity to identify language and communication preferences for discussing their child's weight. Interviews were analyzed for emerging themes. Important trends appeared revealing that parents prefer neutral, medical terms discussed at well-child checks or obesity-specific visits. Providers should frame lifestyle changes as positive for all patients and set achievable goals with the help of visual aids. Our analysis uncovered several important communication strategies that can better equip providers to discuss obesity with their pediatric patients. This research may serve as a foundation for larger studies into the topic.